PENCEGAHAN STUNTING PADA BALITA DAN DETEKSI DINI STUNTING DI PAUD ANNA HUSADA BANGKALAN - Nurun Nikmah; Enggal Sari Maduratna (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2020)
Stunting or also known as "short" is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life. Indonesia is one of the top 5 countries with a high number of children under the age of five who are stunted. The results of the 2015 Nutrition Status Monitoring (PSG) in Indonesia showed that the prevalence of stunting children aged 0-23 months was 23.1%. Based on a survey through interviews with parents of students at PAUD ANNA Husada, it was found that many parents of PAUD Anna Husada’s students still did not know about the prevention of stunting and early detection of stunting. Participants in this activity were 35 mothers and 35 toddlers, PAUD Anna Husada, who participated in training activities and early detection of growth and development. While participating in the activity, the mother was very enthusiastic about the material presented. She was also able to take height measurements and enter into tables to detect stunting. The results of early detection of stunting were found that 5 children under the short category and 1 under the very short category. Mothers also understand the concept of preventing stunting through lactation management and complementary feeding.